2013
DOI: 10.2320/matertrans.m2013028
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a Cylinder-Type Adsorbent for the Recovery of Lithium from Seawater

Abstract: In this work, a spinel lithium manganese oxide (LMO) used as a lithium adsorbent was prepared with a conventional solid state reaction using lithium carbonate and manganese carbonate as the reactants. A cylinder-type LMO was prepared using water glass (sodium silicate solution) as a binder together with the reactants and examined for its lithium adsorption capacity. The effect of the preparation condition on the adsorption capacity of the LMO powder was investigated. The optimum heating condition for the LMO p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…These adsorbents are highly selective to lithium ion and efficient for lithium recovery. However, additional process for the adsorbent such as granulation, membranization for industrial application is necessary, at the same time, leaving the concern for decreasing the capacity or the rate of lithium recovery (Umeno et al, 2002;Ryu et al, 2013b). Also, a couple of weeks of adsorption are followed by adsorbent regeneration using a strong acid.…”
Section: Introductionmentioning
confidence: 99%
“…These adsorbents are highly selective to lithium ion and efficient for lithium recovery. However, additional process for the adsorbent such as granulation, membranization for industrial application is necessary, at the same time, leaving the concern for decreasing the capacity or the rate of lithium recovery (Umeno et al, 2002;Ryu et al, 2013b). Also, a couple of weeks of adsorption are followed by adsorbent regeneration using a strong acid.…”
Section: Introductionmentioning
confidence: 99%
“…The total dissolution of manganese ion is 0.12% or 6.7 mg after 30 cycles, showing that the EP/HMO composite has good stability. In the conventional method, 18,21,22,26,27 the adsorption process is completed when the adsorbent is saturated with Li + , and then the desorption is carried out, which takes a long time for a single cycle (Table 3). In this study, it was observed that the adsorptive efficiency (Figure 7) was higher in the early stage than that in the later stage and 1.25 h was chosen as the adsorption time in the optimized method.…”
Section: Methodsmentioning
confidence: 99%
“…Lithium is the 14th most abundant element in seawater. Its concentration varies across different oceans, despite this it is largely accepted to occur in seawater at a concentration between 0.14 and 0.20 mg/L (Table S3, Supplementary Material [14,17,26,[36][37][38][39][40][41][42]). An average lithium concentration of 0.17 mg/L is often reported.…”
Section: Lithium In Watermentioning
confidence: 99%